Determination of the liquid diffusion coefficient of the Sn-Ni peritectic alloy through temperature gradient zone melting. (April 2020) - Peng, Peng; Yue, Jinmian; Zhang, Anqiao
Highlights: The present method can greatly avoid the influence of solutal convection. The volume fractions of phases are linked to the melt concentration. The liquid migration is linked to the volume fractions of phases. Three stages of liquid migration is analyzed by TGZM. Abstract: In the present work, a new method determining the liquid phase diffusion coefficients DL in a binary peritectic alloy is presented. This method is based on the evolution in both the microstructure and melt concentrations which can be linked through liquid droplet migration in the mushy zone during thermal stabilization. The thermal stabilization experiments of different time (2 to 8 h) are performed on Sn–Ni peritectic alloy (L+Ni3 Sn2 →Ni3 Sn4 ) in a Bridgman-type directional solidification furnace. Two different mushy zones are formed during thermal stabilization of samples which are kept still in the furnace. The diffusion-controlled liquid droplet migration is caused by remelting/resolidification by temperature gradient zone melting (TGZM). It leads to not only the variation of volume fractions of solid( fS )/liquid( fL ) phases in the mushy zone but also the increase of the melt concentration in the complete-liquid zone C . Thus, based on the conservation of mass during thermal stabilization, fS and fL can be correlated to not only the liquid droplet migration velocity vm but also the melt concentration in the complete-liquid zone C during thermal stabilization. Since fS and fL can be easily obtained through microstructure analysis, the experimental value of vm at specific location/temperature is given. Then, the expression of vm which is function of DL is provided by an analytical model describing the remelting/resolidification process during the liquid migration. Finally, DL and the activation energy of the Sn-Ni peritectic alloy are obtained by equating the experimental values of vm with the expression of vm by this analytical model. Graphical Abstract: Image, graphical abstract